Clinical markers of post-Chikungunya chronic inflammatory joint disease: A Brazilian cohort. - Carolina Dos Santos Lázari; Mariana Severo Ramundo; Felipe Ten-Caten; Clarisse S Bressan; Ana Maria Bispo de Filippis; Erika Regina Manuli; Isabella de Moraes; Geovana Maria Pereira; Marina Farrel Côrtes; Darlan da Silva Candido; Alexandra L Gerber; Ana Paula Guimarães; et al. (PLoS Neglected Tropical Diseases)
Background Chikungunya-fever (CHIKF) remains a public health major issue. It is clinically divided into three phases: acute, post-acute and chronic. Chronic cases correspond to 25-40% individuals and, though most of them are characterized by long-lasting arthralgia alone, many of them exhibit persistent or recurrent inflammatory signs that define post-Chikungunya chronic inflammatory joint disease (pCHIKV-CIJD). We aimed to identify early clinical markers of evolution to pCHIKV-CIJD during acute and post-acute phases. Methodology/principal findings We studied a prospective cohort of CHIKF-confirmed volunteers with longitudinal clinical data collection from symptoms onset up to 90 days, including a 21-day visit (D21). Of 169 patients with CHIKF, 86 (50.9%) completed the follow-up, from whom 39 met clinical criteria for pCHIKV-CIJD (45.3%). The relative risk of chronification was higher in women compared to men (RR = 1.52; 95% CI = 1.15-1.99; FDR = 0.03). None of the symptoms or signs presented at D0 behaved as an early predictor of pCHIKV-CIJD, while being symptomatic at D21 was a risk factor for chronification (RR = 1.31; 95% CI = 1.09-1.55; FDR = 0.03). Significance was also observed for joint pain (RR = 1.35; 95% CI = 1.12-1.61; FDR = 0.02), reported edema (RR = 3.61; 95% CI = 1.44-9.06; FDR = 0.03), reported hand and/or feet small joints edema (RR = 4.22; 95% CI = 1.51-11.78; FDR = 0.02), and peri-articular edema observed during physical examination (RR = 2.89; 95% CI = 1.58-5.28; FDR = 0.002). Furthermore, patients with no findings in physical examination at D21 were at lower risk of chronic evolution (RR = 0.41, 95% CI = 0.24-0.70, FDR = 0.01). Twenty-nine pCHIKV-CIJD patients had abnormal articular ultrasonography (90.6% of the examined). The most common findings were synovitis (65.5%) and joint effusion (58.6%). Conclusion This cohort has provided important insights into the prognostic evaluation of CHIKF. Symptomatic sub-acute disease is a relevant predictor of evolution to chronic arthritis with synovitis, drawing attention to joint pain, edema, multiple articular involvement including small hand and feet joints as risk factors for chronification beyond three months, especially in women. Future studies are needed to accomplish the identification of accurate and early biomarkers of poor clinical prognosis, which would allow better understanding of the disease's evolution and improve patients' management, modifying CHIKF burden on global public health.